Homelessness in California - Economic causes - Jakubišin, Marek; Sankot, Ondřej, 1988-; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines economic factors contributing to homelessness in the US with a focus on California, specifically housing costs, income inequality, rent burden, housing availability, and regulatory issues. By comparing California with New York and Florida, states with comparable populations and income inequality levels, the study mainly utilizes data from 2010 to 2023 from the U.S. Census Bureau and the Department of Housing and Urban Development. The analysis explores how these economic elements and regulatory frameworks interact differently across states, impacting homelessness.
Vedoucí práce: Ondřej Sankot
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses